Aspects of Comparative Literature: A Selective, Yet Stimulating Introduction to Boundary-Crossing Literary Studies (KULT_online, 2012)
Ernst Grabovszki's introduction to Comparative Literature offers a basic outline of the discipline’s key topics and methods and its epistemological grounds. The author puts a special focus on the importance of inter- and transdisciplinary literary studies for Comparative Literature as a discipline dealing with literature and culture in a global context. The three main chapters of the book offer a re-definition of the notion of 'world literature', aim at mapping the status of literature in the context of recent developments of cultural globalization, and problematize the method of comparison, while other sections thematize the relevance of intermedial approaches and translation studies for Comparative Literature and sketch the history of the discipline since its 19th century beginnings.